LncRNA LINC00667 aggravates the progression of hepatocellular carcinoma by regulating androgen receptor expression as a miRNA-130a-3p sponge - Zhixiang Qin; Xiaohong Liu; Zijing Li; Ganggang Wang; Zhe Feng; Ye Liu; Hai Yang; Chengpeng Tan; Zidong Zhang; Kun Li (Cell Death Discovery, 2021)
Abstract Emerging studies have found long noncoding RNAs, widely expressed in eukaryotes, crucial regulators in the progression of human cancers, including hepatocellular carcinoma (HCC). Although the long intergenic noncoding RNA 667 (LINC00667) can promote the progression of a variety of cancer types, the expression pattern, the role in cancer progression, and the molecular mechanism involved in HCC remain unclear. This study aims to investigate the function and mechanism of LINC00667 in HCC progression. The effects of LINC00667 silencing in cell proliferation, cell migration, and cell invasion, and androgen receptor (AR) expression were determined with loss-of-function phenotypic analysis in Huh-7 and HCCLM3 cells, and subsequently testified in vivo in tumor growth. We found that the expression of LINC00667 was upregulated in HCC tissues and cell lines. Upregulation of LINC00667 was significantly associated with the unfavorable prognosis of HCC in our study patients. On the other hand, low expression of LINC00667 significantly inhibited the cell proliferation, cell migration and cell invasion of HCC in vitro and tumor growth in vivo. This inhibitory effect could be counteracted by miR-130a-3p inhibitor. LINC00667 reduced the inhibition of AR expression by miR-130a-3p, which correlated with the progression of HCC. Our finding suggests LINC00667 is a molecular sponge in the miR-130s-3p/AR signal pathway in the progression of HCC, in which it relieves the repressive function of miR-130a-3p on the AR expression. This indicates LINC00667 functions as a tumor promotor in promoting HCC progression through targeting miR-130a-3p/AR axis, making a novel biomarker and potential therapeutic target for HCC.